PENGARUH HUMBLE LEADERSHIP DAN INCLUSIVE LEADERSHIP TERHADAP INNOVATIVE BEHAVIOR DI MEDIASI OLEH WORK ENGAGAMENT PADA PERUSAHAAN STARTUP DI JAKARTA - Irma Febri Damayanti; Ratri Ayu Asmorofitri; Netania Emilisa; Chaterine Febriyani (Politeknik Bisnis Indonesia, 2024)
This research aims to analyze Humble leadership and Inclusive Leadership on Innovation Behavior in Mediation, the influence of Humble Leadership, the influence of Inclusive Leadership, and 4. the influence of Humble Leadership on Innovation behavior of employees in Startup companies. This research applies a quantitative descriptive approach and data analysis is carried out through hypothesis testing which is used to assess the correlation between variables to test the influence of Humble Leadership, Inclusive Leadership, mediated by Work Engagement on Innovative Behavior in employees at startup companies in Jakarta.